Pengaruh Current Ratio Dan Debt To Equity Ratio Terhadap Return On Equity Pada Perusahaan Sub Sektor Kontruksi Dan Bangunan Yang Terdaftar Di Bursa Efek Indonesia Periode 2019 – 2021 - Renhardt Bimantoro Brojo Negoro; Anwar Bowo Leksono; Suseno Hendratmoko (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
This research aims to see the ability of the Current Ratio and Debt to Equity Ratio to Return On Equity in the Construction and Building Sub-Sector listed on the Indonesian Stock Exchange for the 2019 - 2021 period. Using financial reports obtained from the Indonesian Stock Exchange with purposive sampling as the sampling method in this research. This research uses panel data regression analysis, namely Descriptive Analysis, Statistical Analysis: Chow Test, Hausman Test, Lagrage Multipler Test, Prerequisite Test: Normality Test, Multicollinearity Test, Heteroscedasticity Test, Hypothesis Test: t Test, f Test and Determinant Coefficient Test with e-views program assistance10. The research results show that together the variables Current Ratio and Debt to Equity Ratio have a simultaneous and significant effect on Return On Equity. The coefficient of determination test shows that it is 75% while the remaining 25% is influenced by other factors outside the research. Partially, the Current Ratio has no effect at 0.0446 and the t-statistic is 2.206494. Partially, the Debt to Equity Ratio has a positive and significant effect of 0.0632 and the t-statistic is -2.017908.